Electrospray ion beam deposition plus low-energy electron holography as a tool for imaging individual biomolecules. Issue 2 (29th March 2023) - Ochner, Hannah; Rauschenbach, Stephan; Malavolti, Luigi
Abstract: Inline low-energy electron holography (LEEH) in conjunction with sample preparation by electrospray ion beam deposition (ES-IBD) has recently emerged as a promising method for the sub-nanometre-scale single-molecule imaging of biomolecules. The single-molecule nature of the LEEH measurement allows for the mapping of the molecules' conformational space and thus for the imaging of structurally variable biomolecules, thereby providing valuable complementary information to well-established biomolecular structure determination methods. Here, after briefly tracing the development of inline LEEH in bioimaging, we present the state-of-the-art of native ES-IBD + LEEH as a method of single-protein imaging, discuss its applications, specifically regarding the imaging of structurally flexible protein systems and the amplitude and phase information encoded in a low-energy electron hologram, and provide an outlook regarding the considerable possibilities for the future advancement of the approach.